2014
DOI: 10.1182/blood-2013-08-523233
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-130a regulates C/EBP-ε expression during granulopoiesis

Abstract: Key Points miRNA-130a is expressed in myeloblasts and promyelocytes and inhibits translation of CEBPE mRNA encoding transcription factor C/EBP-ε. Regulation of CEBPE mRNA by miRNA-130a is required for timed expression of secondary granule proteins and cell cycle exit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Transcription of miR-130a is governed by the proto-oncogene c-Myc [34,35], a wellcharacterized driver of cell proliferation through induction of cyclins and repression of p21Kip1 transcription [36,37]. Expression of c-Myc is high in MB/PMs and low in more mature cells as seen also for miR-130a further indicating a role for miR-130a as regulator of cell proliferation [25].…”
Section: Mirnas and Transcription Factorsmentioning
confidence: 94%
See 3 more Smart Citations
“…Transcription of miR-130a is governed by the proto-oncogene c-Myc [34,35], a wellcharacterized driver of cell proliferation through induction of cyclins and repression of p21Kip1 transcription [36,37]. Expression of c-Myc is high in MB/PMs and low in more mature cells as seen also for miR-130a further indicating a role for miR-130a as regulator of cell proliferation [25].…”
Section: Mirnas and Transcription Factorsmentioning
confidence: 94%
“…The CEBPE transcript, on the other hand, is present also in MB/PMs, and to avoid premature translation of C/EBP-ε downregulation by miR-130a is required. This is demonstrated by the untimely expression of C/EBP-ε in MB/PMs transfected with a Locked Nucleic Acid (LNA) oligo against miR-130a and by repression of C/EBP-ε and genes encoding secondary granule proteins, by forced expression of miR-130a [25]. During normal granulopoiesis the level of miR-130a is 8-10 times higher in MB/PMs than in more mature neutrophil precursors in accordance with a role as fine-tuner of C/EBP-ε expression in MB/PMs [13].…”
Section: Mirnas and Transcription Factorsmentioning
confidence: 95%
See 2 more Smart Citations
“…miR-130a was observed to be downregulated in pancreatic cancer and CML (5,6). miR-130a is a c-myc-responsive gene, which has been identified to regulate CCAAT/enhancer-binding protein β, homeobox A5, runt-related transcription factor 3 and Wnt signaling (33)(34)(35). Previous studies have demonstrated that the expression of miR-130a is increased in non-small cell lung cancer (36), whereas in glioblastoma patients, increased levels of miR-130a are associated with long-term survival (37).…”
Section: Mir-15 Mir-15 Was Identified To Be Downregulated In Screensmentioning
confidence: 99%